Patterns of Export Diversification In Developing Countries : Intensive And Extensive Margins - Amurgo-Pacheco, Alberto (The World Bank, 2008)
This paper uses highly disaggregated trade data to investigate geographic and product diversification patterns across a group of developing nations for the period from 1990 to 2005. The econometric investigation shows that the gravity equation fits the observed differences in diversification across nations. The analysis shows that exports at the intensive margin account for the most important share of overall trade growth. At the extensive margin, geographic diversification is more important than product diversification, especially for developing countries. Taking part in free trade agreements, thereby reducing trade costs, and trading with countries in the North are also found to have positive impacts on export diversification for developing countries